Foraging behavior of Raramuri Criollo vs. Angus cattle grazing California Chaparral and Colorado Plateau shrublands. (June 2023) - Duni, Danielle M.; McIntosh, Matthew M.; Nyamuryekung'e, Shelemia; Cibils, Andres F.; Duniway, Michael C.; Estell, Richard E.; Spiegal, Sheri A.; Gonzalez, Alfredo L.; Gedefaw, Melakeneh G.; Redd, Matthew; Paulin, Robert; Steele, Caitriana M.; et al.
Abstract: Selecting livestock genetics adapted to arid environments, such as Criollo cattle, is one of several strategies recommended for decreasing the vulnerability to climate change of ranching in the southwestern USA. Our objective was to determine whether desirable foraging traits of Criollo cattle previously documented in the Chihuahuan Desert, held true in two of the most climate-vulnerable ecosystems of the Southwest. We conducted a study at Rancho Corta Madera (RCM) in southern California and Dugout Ranch (DR) in southeast Utah. Twenty mature cows, 10 Raramuri Criollo and 10 Red or Black Angus, were monitored with GPS collars during multiple seasons between 2018 and 2021. Geolocation data were used to compute daily distance traveled (km*d −1 ), movement velocity (m*min −1 ), path sinuosity (SI), time spent grazing, resting, or traveling (h*d −1 ), and area of the pasture explored (ha*d −1 ) as well as to calculate selection of vegetation cover types ( E, Ivlev's Electivity Index) by cows of each breed. The effects of breed, season, year, and pasture on each of these metrics were modeled with repeated measures analyses of variance. At both ranches, statistically detectable differences (P ≤ 0.05) between breeds were observed for most behavior metrics during the dormant season. Conversely, few breed differences were observed during the growing season. Criollo cattle exhibited greater relative preference for a number of shrub dominated vegetation types at both ranches, and similar relative selection of grassland dominated sites compared to Angus counterparts. At both ranches, Criollo cattle exhibited similar or less relative preference for riparian areas vs. Angus counterparts. Breed divergence vs. convergence of foraging behaviors during the dormant vs. growing seasons, previously observed in the Chihuahuan Desert, was documented at both sites. Positive system outcomes associated with foraging traits of Criollo cattle could be expected to occur more broadly across the Southwest.